Kinetic Modeling of Ni and Co Adsorption: A Comparative Study on Activated Zeolite - Fikrah Dian Indrawati Sawali; Moh. Azhar Afandy (Institut Teknologi Nasional, Bandung, 2026)
AbstractThe existence of heavy metals such as nickel (Ni) and cobalt (Co) can lead to environmental problems that have an immediate impact on human life, therefore it is crucial to carry out proper preventative strategies in wastewater treatment, one of the these utilizes the process of adsorption. In the current investigation, thermally activated zeolite (ZT) by a carbonization process at a temperature of 550°C was utilized as a medium in the adsorption phase of Ni and Co from simulated wastewater with variation in a mass ratio of ZT. Several kinetic models have been used for evaluating the kinetic parameters and mechanisms that control the adsorption process. The outcomes received shown the adsorption process of Ni and Co by ZT followed the PSO kinetic model (R² > 0.99) with qe = 9.4877 mg.g⁻¹ and k₂ = 329.6075 g.mg⁻¹.min⁻¹ for Ni and qe = 7.3206 mg.g⁻¹ .min⁻¹ and k₂ = 127.9652 g.mg⁻¹.min⁻¹ for Co. Based on the PSO kinetic model, it can be assumed that the adsorption process of Ni and Co by ZT is controlled by chemical interactions through ion exchange and the creation of coordination covalent bonds with active sites on the surface of the adsorbent.Keywords: Adsorption, Nickel, Cobalt, Zeolite